Risk Analysis in Public–Private Partnership (PPP) Schemes for Infrastructure Development in Indonesia: A Case Study of the Serang–Panimbang Toll Road Project, Section 2 - Siti Asyiah; Rifky Ujianto; Mush'ab 'Abdu Asy Syahid; Dwi Novi Setiawati; Annisa Rahman Tabrani Putri (Jurnal Fondasi, 2026)
The limited capacity of the State Budget (APBN) to finance infrastructure development has led to a significant funding gap that must be addressed. To overcome this challenge, the Government has adopted an alternative financing scheme known as Public–Private Partnership (PPP). PPP is defined as a collaborative arrangement between the Government and private entities in the provision of infrastructure aimed at serving public interests. This study aims to identify the risks associated with the implementation of the PPP scheme in the Serang–Panimbang Toll Road Project, Section 2, and to determine appropriate strategies for risk mitigation and response. The research employs a quantitative approach using descriptive analysis. Risk assessment is conducted by comparing the Severity Index and the Probability Index to determine the level of risk. The results show that the majority of identified risks fall into high and extreme categories, with 15 variables classified as extreme risk, 23 variables as high risk, and 1 variable as moderate risk. The most critical risks are related to land acquisition, project scope changes, limited working space, geological conditions, and permitting processes, particularly during the pre-construction and construction phases. Mitigation strategies emphasize the importance of contractual clarity, stakeholder coordination, technical investigation, and financial preparedness, with several risks requiring shared responsibility between the government and private sector. These findings highlight the importance of proactive and integrated risk management to improve the performance and sustainability of PPP-based infrastructure projects.